An integrative approach to the delimitation of pseudocryptic species in the Eucyclops speratus complex (Copepoda, Cyclopoida) with a description of a new species - Aleksandr Novikov; Dayana Sharafutdinova; Ekaterina Abramova; Tatyana Mayor; Elena Chertoprud (ZooKeys)
Eucyclops speratus (Lilljeborg, 1901) (Copepoda, Cyclopoida, Cyclopidae) was studied using various methods. Molecular genetic methods (comparison of COI and ITSn molecular markers) have shown that this species represents a species complex, and the following methods were used to search for differences between the species: analysis of qualitative and quantitative characters, linear morphometrics, landmark-based geometric morphometrics, and integumental pore pattern of the cephalothorax. Eucyclops sibiricus sp. nov. from Middle Siberia is described. The two studied species can be considered pseudocryptic; the main morphological difference between the species is the number of setules on the inner side of the first and second exopod segments of the fourth pair of swimming legs: E. sibiricus sp. nov. has 6–10 and 7–17 setules, respectively; E. speratus has 0–3 and 0–6 setules, respectively. The morphometry and integumental pore pattern of the cephalothorax were ineffective for identification and separation of species. The existing previous records of E. speratus were also analyzed, and the records of this species in the Irkutsk region (Russia), as well as in Japan and Korea, are attributed to E. sibiricus sp. nov.